Georgia Architectural and Historic Properties Survey of Ga. 90, Rebecca, Turner County, Ga., March 1981 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Ga. 90, Rebecca, Turner County, Ga., March 1981. 1 story rectangular clapboard house with gabled and hipped roof; hipped porch supported by tapered square posts; 1/1 double sash windows, interior chimneys, and gabled dormers with shingles are features of this structure; a bay at left front is also featured. Fair condition. Date of Construction: c. 1905. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Ga. 90, Rebecca, Turner County, Ga., March 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 54.0 MB (56,715,867 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Rebecca (Ga.); Turner County (Ga.)